Invisible Shields: How cryptography Safeguards our digital lives (International Journal of Food and Nutritional Sciences, 2022)
Ensuring the integrity and confidentiality of voting processes is paramount in democraticsocieties. Traditional voting systems face numerous challenges, including ballot tampering, coercion,and logistical constraints. In response, cryptographic techniques have emerged as a promising solutionto mitigate these vulnerabilities and enhance the security of electoral systems.